The link between mobile telephony arrears and credit arrears - Helga De Doncker (National Bank of Belgium, 2011)
At the request of the Minister for Climate and Energy, Paul Magnette, who is also responsible for Consumer Affairs, the NBB's Microeconomic Analysis Service conducted an investigation into the link between payment arrears for mobile telephony and arrears on loan repayments. In this inquiry, which was carried out using data drawn from the Preventel records and from the Central Individual Credit Register, the profile of people with arrears for both types of debt was also analysed. The profile analysis shows that defaulters with a Preventel registration form a specific group among CICR defaulters. People with payment arrears for both types of debt tend to have a demographic and credit profile which to a large extent matches that of CICR defaulters with no mobile phone payment arrears, but a few differences were also found between both groups of defaulters. A number of trends in borrowing and repayment behaviour turn out to be much more pronounced in the first of these two defaulter groups, but it is above all in regard to the age aspect that the differences are most striking. In cases where people have fallen behind in their payments for both types of debt, it actually turns out to be a younger group. Generally speaking, these borrowers take out their first loan at an earlier age, and they also tend to run up their first arrears when they are younger. The inquiry further revealed that there is a statistically significant link between payment arrears for mobile telephony and credit arrears, and this applies for various definitions of payment arrears. Repayment problems generally tend to emerge sooner in payment arrears for mobile telephony bills than in arrears on loans. A simple logistic regression model indicates that dummy variables for a Preventel registration, and for the duration of that registration, still have a definite predictive value with regard to credit arrears, after controlling for a number of demographic and credit variables in the model. As the assessment of the credit risk of private individuals is based on a set of socio-economic variables, payment arrears for mobile telephony could therefore be a useful complementary variable in that assessment.
Keywords: D14; D18; G21; G29; L96; 330; consumer credit bureau; credits; mobile telephony; payment arrears; Kredittilgung; Insolvenz; Zahlungsverhalten; Mobiltelefon; Privater Haushalt; Belgien; Luxemburg